Λ-particle energies from the (π+.Κ+) associated production reaction on nuclei and the state dependence of the Λ-nucleus potential - Lalazissis, G. A. (HNPS Advances in Nuclear Physics, 2019)
A Λ-nucleus potential of the symmetrized Woods-Saxon type is mainly used and the Λ-particle energies deduced from the (π+ ,K+) associated production reaction on nuclei are analysed by a least squares fitting. Although a firm quantitative conclusion about the state dependence of the Λ-nucleus potential cannot be drawn on the basis of the existing data from the (π+,.Κ'+) process, it appears that this dependence is quite weak, as it should be also expected on the basis of other studies. The present analysis indicates that the depth of the symmetrized Woods-Saxon Λ-nucleus potential in the lp-state is somehow smaller than the depth in the ls-state, while the range of the potential is slightly longer.